HMA6 and HMA8 are two chloroplast Cu+-ATPases with different enzymatic properties. Issue 3 (11th June 2015) - Sautron, Emeline; Mayerhofer, Hubert; Giustini, Cécile; Pro, Danièle; Crouzy, Serge; Ravaud, Stéphanie; Pebay-Peyroula, Eva; Rolland, Norbert; Catty, Patrice; Seigneurin-Berny, Daphné
Abstract : In Arabidopsis chloroplasts, HMA8, the thylakoid Cu + -ATPase and HMA6, the envelope Cu + -ATPase, have different enzymatic properties. These differences might be related to the electrostatic properties of the Cu + release cavities of the transporters or the nature of their Cu acceptor. Abstract : Copper (Cu) plays a key role in the photosynthetic process as cofactor of the plastocyanin (PC), an essential component of the chloroplast photosynthetic electron transfer chain. Encoded by the nuclear genome, PC is translocated in its apo-form into the chloroplast and the lumen of thylakoids where it is processed to its mature form and acquires Cu. In Arabidopsis, Cu delivery into the thylakoids involves two transporters of the PIB-1 ATPases family, heavy metal associated protein 6 (HMA6) located at the chloroplast envelope and HMA8 at the thylakoid membrane. To gain further insight into the way Cu is delivered to PC, we analysed the enzymatic properties of HMA8 and compared them with HMA6 ones using in vitro phosphorylation assays and phenotypic tests in yeast. These experiments reveal that HMA6 and HMA8 display different enzymatic properties: HMA8 has a higher apparent affinity for Cu + but a slower dephosphorylation kinetics than HMA6. Modelling experiments suggest that these differences could be explained by the electrostatic properties of the Cu + releasing cavities of the two transporters and/or by the different nature of their cognate Cu + acceptors (metallochaperone/PC).